2017
DOI: 10.1161/strokeaha.116.016253
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Thrombus Length on Outcomes After Intra-Arterial Aspiration Thrombectomy in the THERAPY Trial

Abstract: Background and Purpose-Increasing thrombus length (TL) impedes recanalization after intravenous (IV) thrombolysis.We sought to determine whether the clinical benefit of aspiration thrombectomy relative to IV r-tPA (recombinant tissuetype plasminogen activator) may be greater at longer TL. Methods-THERAPY was a randomized trial of aspiration thrombectomy plus IV r-tPA versus IV r-tPA alone in largevessel stroke patients with prospective TL measurement ≥8 mm. In this post hoc study, we evaluated the association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 19 publications
(20 reference statements)
8
26
0
Order By: Relevance
“…Although there are conflicting data, 13À15 clot length has been associated with decreased reperfusion rate and worse outcome. 16 In fact, the odds ratio for worse outcomes increases by 1.24 for every 5 mm increment over 14 mm. 16 An independent risk factor for stroke (odds ratio 3.4À14.5 17 ) is an inflammation-driven 18 hypercoagulable and vasculopathic state 19 from recent infection, especially respiratory in origin.…”
Section: Discussionmentioning
confidence: 98%
“…Although there are conflicting data, 13À15 clot length has been associated with decreased reperfusion rate and worse outcome. 16 In fact, the odds ratio for worse outcomes increases by 1.24 for every 5 mm increment over 14 mm. 16 An independent risk factor for stroke (odds ratio 3.4À14.5 17 ) is an inflammation-driven 18 hypercoagulable and vasculopathic state 19 from recent infection, especially respiratory in origin.…”
Section: Discussionmentioning
confidence: 98%
“…7,10 Besides, longer thrombi may be more difficult to retrieve, requiring more attempts and prolonging the procedural time. 7,31 Few studies have assessed the relation between collateral status and clot extent and the role of collateral status in the association of clot extent with functional outcome. 13,14 Our findings are in accordance with previous studies in which patients with poor baseline collaterals had longer clots.…”
Section: Discussionmentioning
confidence: 99%
“…In the ESCAPE trial, Puetz et al [22] demonstrated an increase in benefit from MT for lower CTA-CBS, i.e., longer thrombus, when compared with higher CTA-CBS. Similarly, in a post hoc analysis of 108 patients included in the THERAPY trial [14], longer thrombi, as defined on CTA, were independently associated with worse clinical outcomes. Furthermore, in adjusted analyses of 90-day ordinal mRS, there was a 33% relative increase in the likelihood of a worse outcome with every 5-mm increase in thrombus length and the relative benefit of MT compared with IVT alone increased with thrombus length [14].…”
Section: Discussionmentioning
confidence: 99%
“…Amongst factors influencing recanalization success, clot length is an important determinant [10-12], that was scarcely assessed in the recent RCTs. Indeed, if patients were included in case of LVO on computed tomography angiography (CTA), only few studies [13,14] assessed clot length using the CTA-defined clot burden score (CTA-CBS). These analyses demonstrated a direct link between clot length, likelihood of recanalization, final infarct volumes, and 3-month neurological outcome.…”
Section: Introductionmentioning
confidence: 99%